The origins of Prussia : by F.L. Carsten - Carsten, F. L. (Francis Ludwig)
En contracubierta: Oxford University Press | Bibliografía: p. [289]-295. Índice | Índice de contenidos: The colonization -- The rise of the Junkers -- The foundation of the Hohenzollern despotism.